2018
DOI: 10.3389/fimmu.2018.01040
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides fragilis Protects Against Antibiotic-Associated Diarrhea in Rats by Modulating Intestinal Defenses

Abstract: Antibiotic-associated diarrhea (AAD) is iatrogenic diarrhea characterized by disruption of the gut microbiota. Probiotics are routinely used to treat AAD in clinical practice; however, the effectiveness and mechanisms by which probiotics alleviate symptoms remain poorly understood. We previously isolated a non-toxic Bacteroides fragilis strain ZY-312, which has been verified to be beneficial in certain infection disorders. However, the precise role of this commensal bacterium in AAD is unknown. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 53 publications
4
60
0
3
Order By: Relevance
“…In our experiments, in addition to confirming that soft feces (increased fecal water content) was induced by the oral administration of metformin by gavage three times per day, we also confirmed changes in the gut microbiota, especially a tendency for a decrease in Lactobacillus species and a significant increase in Staphylococcus species. A decrease in Lactobacillus species and an increase in Staphylococcus species have also been confirmed for antibiotic-associated diarrhea (AAD) [ 14 ]. Furthermore, other studies have suggested that Lactobacillus administration improves AAD [ 15 ] and that the presence of Staphylococcus species is related to AAD [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, in addition to confirming that soft feces (increased fecal water content) was induced by the oral administration of metformin by gavage three times per day, we also confirmed changes in the gut microbiota, especially a tendency for a decrease in Lactobacillus species and a significant increase in Staphylococcus species. A decrease in Lactobacillus species and an increase in Staphylococcus species have also been confirmed for antibiotic-associated diarrhea (AAD) [ 14 ]. Furthermore, other studies have suggested that Lactobacillus administration improves AAD [ 15 ] and that the presence of Staphylococcus species is related to AAD [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ZY-312 has been shown to be able to inhibit the growth and adhesion of Vibrio parahaemolyticus ( V. parahaemolyticus ) in vitro and protect both RAW 264.7 and LoVo cells from damage caused by V. parahaemolyticus ( Li et al, 2017 ). Recently, we discovered the modulatory effect of ZY-312 on gut microbiota in rats, which contributes to the amelioration of antibiotic-associated diarrhea ( Zhang et al, 2018 ). In general, ZY-312 has the potential to become the first probiotic representative of the dominant Bacteroidetes phylum.…”
Section: Discussionmentioning
confidence: 99%
“…GI commensal microbiota profile (enterotype) varied across geographical regions in a continuous matter [17][18][19]. It is apparent that the GI microenvironment and microbial community among Southeast Asian are not favourable for the establishment and proliferation of Bifidobacterium and Bacteroides, both of each have been suggested to play major roles in maintenance of health and are probiotics [7,[20][21][22][23]. It is reasonable to assume that Bifidobacterium and Bacteroides probiotics may need to be administered together with prebiotics (as synbiotic) for people in the South-East Asian.…”
Section: Microbe-microbe Interaction In Gastrointestinal (Gi) Environmentioning
confidence: 99%
“…It is therefore not surprising that beneficial effects of complex carbohydrate utilizing probiotics, such as Bifidobacterium spp. are amplified among East Asian [18,22] while meat-fat eating European and American may benefit from Bacteroides probiotics [21,23,55]. Selected strains of the respective bacteria group may serve as potent probiotics, if they are not already pleasant among the commensals, for people of different dietary habit.…”
Section: Microbe-diet Interactionmentioning
confidence: 99%
See 1 more Smart Citation